1990
DOI: 10.1002/aic.690360808
|View full text |Cite
|
Sign up to set email alerts
|

Rationalization for the molecular weight distributions of Coal pyrolysis liquids

Abstract: A model for coal thermal depolymerization is described and used to predict molecular weight distributions (MWD) of primary coal pyrolysis liquids. The model assumes that rupture of kinetically similar bonds in the coal is the preferred pathway for release of oligomers which ultimately become tars or extractables. The analysis provides the liquids MWD as a probability function of finding different oligomers composed of whole integer numbers of monomers and it is in excellent qualitative agreement with measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…versatile representation of naturally distributed systems (e.g., Darivakis et al, 1990;Wang et al, 1994), and is chosen to represent the MWDs,…”
Section: Continuous Kinetics Of Chain Scissionmentioning
confidence: 99%
“…versatile representation of naturally distributed systems (e.g., Darivakis et al, 1990;Wang et al, 1994), and is chosen to represent the MWDs,…”
Section: Continuous Kinetics Of Chain Scissionmentioning
confidence: 99%
“…This MWD varied with time and, according to the model, eventually yielded a mixture of molecules ali having an identical, minimum MW. Darivakis et al (1990) applied probabtlity theory to develop a model for coal thermolysts to showed that a gamma distribution function can successfully fit experimental MWD data. Although the model interpreted the MWDs of pyrolysis products, it did not consider rate expressions for the thermolysis reactions.…”
Section: Nomenclaturementioning
confidence: 99%
“…Here we present a rate theory based in part upon the concepts presented by Darivakis et al (1990) and combined with concepts of continuous-mixture kinetics. The model builds on earlier approaches, and introduces the following novel features: • Regular polyaromatic units connected tnto the main structure by two linkages.…”
Section: Nomenclaturementioning
confidence: 99%
See 2 more Smart Citations